Comparative Genomics of Members of the Genus Defluviicoccus With Insights Into Their Ecophysiological Importance - Bessarab, Irina; Maszenan, Abdul Majid; Haryono, Mindia A. S.; Arumugam, Krithika; Saw, Nay Min Min Thaw; Seviour, Robert J.; Williams, Rohan B. H. (Frontiers in Microbiology, 2022)
Members of the genus Defluviicoccus occur often at high abundances in activated sludge wastewater treatment plants designed to remove phosphorus, where biomass is subjected to alternating anaerobic feed/aerobic famine conditions, believed to favour the proliferation of organisms like Ca. Accumulibacter and other phosphate accumulating organisms (PAO), and Defluviicoccus. All have a capacity to assimilate readily metabolizable substrates and store them intracellularly during the anaerobic feed stage so that under the subsequent famine aerobic stage these can be used to synthesize polyphosphate reserves by the PAO and glycogen by Defluviicoccus. Consequently, Defluviicoccus is described as a glycogen accumulating organism or GAO. Because they share a similar anaerobic phenotype, it has been proposed, that at high Defluviicoccus abundance, the PAO are out-competed for assimilable metabolites anaerobically, and hence aerobic P removal capacity is reduced. Several Defluviicoccus whole genome sequences have been published (Ca. Defluviicoccus tetraformis, Defluviicoccus GAO-HK and Ca. Defluviicoccus seviourii). The available genomic data of these suggest marked metabolic differences between them, some of which have ecophysiological implications. Here we describe the whole genome sequence of the type strain Defluviicoccus vanusT, the only cultured member of this genus, and a detailed comparative re-examination of all extant Defluviicoccus genomes. Each, with one exception, which appears not to be a member of this genus, contains the genes expected of GAO members, in possessing multiple copies of those for glycogen biosynthesis and catabolism, and anaerobic polyhydroxyalkanoate (PHA) synthesis. Both 16S rRNA and genome sequence data suggest that the current recognition of four clades is insufficient to embrace their phylogenetic biodiversity, but do not support the view that they should be re-classified into families other than their existing location in the Rhodospirillaceae. As expected, considerable variations were seen in the presence and numbers of genes encoding properties associated with key substrate assimilation and metabolic pathways. Two genomes also carried the pit gene for synthesis of the low affinity phosphate transport protein, pit, considered by many to distinguish all PAO from GAO. The data re-emphasise the risks associated with extrapolating the data generated from a single Defluviicoccus population to embrace all members of that genus.